Comparing the analgesic effects of ultrasound-guided caudal block and dorsal penile nerve block in pediatric concealed penis correction surgery: a randomized controlled trial - Lin, Zhuopeng; Shao, Yunhao; Li, Huidong; Chen, Zhifeng; Li, Yanfei; Wu, Shuhuan; Liu, Nian; Zhang, Zhongqi (Frontiers in Pediatrics, 2025)
BackgroundEffective perioperative analgesia is critical for pediatric patients undergoing concealed penis correction surgery. Despite the utility of regional techniques like caudal block (CB) and dorsal penile nerve block (DPNB), evidence comparing their efficacy in this population remains limited. This study aimed to compare ultrasound-guided CB and DPNB for perioperative analgesia in pediatric concealed penis surgery.MethodsIn this prospective, double-blind, randomized controlled trial, 86 children (aged 5–12 years, ASA I–II) were allocated to CB (n = 44) or DPNB (n = 42) groups. All the children were induced with general anesthesia using propofol and sevoflurane, followed by laryngeal mask placement. Anesthesia was maintained with sevoflurane inhalation (spontaneous respiration preserved) under depth-of-anesthesia monitoring. The CB group received ultrasound-guided CB, while the DPNB group underwent bilateral dorsal penile nerve block, both using 0.2% ropivacaine. Primary outcomes included postoperative analgesic requirements within 24 h. Secondary outcomes encompassed pain scores, hemodynamic parameters, adverse events, and satisfaction.ResultsThe CB group demonstrated significantly lower analgesic requirements (38.6% vs. 71.4%, p = 0.005) within 24 h and reduced early postoperative pain scores (at 2,4,6 h, p < 0.05). Intraoperatively, CB required fewer anesthesia deepening (20.5% vs. 52.4%, p = 0.004) and shorter surgical duration (71.1 ± 13.7 vs. 79.7 ± 9.9 min, p = 0.001). Adverse events, including tachycardia (2.3% vs. 26.2%, p = 0.004) and body movements (6.8% vs. 42.9%, p < 0.001), were less frequent with CB. Parental and surgeon satisfaction were higher in the CB group (p = 0.049 and p < 0.001).ConclusionsUltrasound-guided CB provides superior perioperative analgesia, fewer complications, and higher satisfaction compared to DPNB in pediatric concealed penis surgery, supporting its preference for this specific procedure in clinical practice. Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=178288, identifier ChiCTR2200065359.